Bone cancer detection using electrical impedance tomography - Nabanita Saha; Mohammad Anisur Rahaman (Institute of Advanced Engineering and Science, 2021)
Bone cancer is an uncommon sort of malignancy that alludes to irregular development of tissue inside the bone, with high opportunity to spread to different pieces of the body. It is extremely important to distinguish bone cancer at the beginning phase to cure it productively. Presently, in addition to a physical examination, magnetic resonance imaging, blood tests, positron emission tomography (PET), computed tomography (CT) or PET-CT scan, X-ray, Bone scan, Biopsy and computed tomography scan, are used to diagnose or determine the stage (or extent) of bone sarcoma. But these methods are costly and not free of radiation. Moreover, these machines are bulky. Electrical impedance tomography approach was proposed in this research for identifying bone cancer as this detection technique is able to distinguish between cancerous and non-cancerous cells by differentiating between their conductivity and it has the possibility to remove the limitations of conventional medical imaging techniques. Here, equivalent bone models were generated using (electrical impedance and diffused optical reconstruction software (EIDORS) which had been implemented in MATLAB, and three different image reconstruction algorithms-GREIT, Sheffield Backprojection, Gauss-Newton inverse algorithm had been used to detect the cancerous cells.